Pengaruh Sikap, Harga dan Kualitas Produk terhadap Minat beli Dodol Nanas Sebagai Komoditas Unggulan Kabupaten Mempawah - Yuni Firanyanti; Edy Suchmawan; Didik Didik; Marhamah Marhamah; Siti Romlah (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to determine the influence of attitudes on the interest in buying pineapple dodol as a superior commodity in Galang Village, Sungai Pinyuh District, to determine the effect of price on the interest in buying pineapple dodol as a superior commodity in Galang Village, Sungai Pinyuh District, and to determine the effect of quality on the interest in buying pineapple dodol as a superior commodity in Galang Village, Sungai Pinyuh District. This study uses a quantitative research method. The population in this study were pineapple dodol consumers in Galang Village, Sungai Pinyuh District with a population of 4000 and a sample of 98 respondents. The sampling method used a purposive sampling technique with data collection techniques using a questionnaire. Data analysis in this study includes descriptive statistical analysis test, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test and coefficient of determination test, T test, F test with IBM SPSS 25 tools. The results of the T Test can be concluded that Attitude has a significant effect on purchasing interest, Price has a significant effect on purchasing interest, Product quality has a significant effect on purchasing interest, The results of the F Test analysis can be concluded that the variables of attitude, price and product quality simultaneously influence the purchasing interest of Pineapple dodol as a superior commodity in Galang Village, Sungai Pinyuh District.